Answer:
D
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
To calculate m use the slope formula
m = ( y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (3, 6) and (x₂, y₂ ) = (8, 4)
m = = - , hence
y = - x + c ← is the partial equation
To find c substitute either of the 2 points into the partial equation
Using (8, 4), then
4 = - + c ⇒ c = 4 + =
y = - x + ← equation of line
Answer:
slope(m)=change in y/change in x
6=y-(-1)/x-4
6=y+1/x-4
6(x-4)=y+1
6x-24=y+1
6x-24-1=y
6x-25=y
hence this is the equation
Answer:
3 < 5
Step-by-step explanation:
3 < 5
We can write this inequality, because three is less than five, and < means less than.
Answer:
∠AZ = ∠BX
The two triangles are equivalent triangles
Step-by-step explanation:
Flowchart proofs are organized with boxes and arrows. The statements given are written in the box and the reason of that statement is written just below the box. Every statement if flowchart proof complements other statement.
∠AZ = ∠BX
The two triangles are equivalent triangles.